Treatment of Cartilage Injury in Rat’s Knee Joint by Implantation of A 3-D Silk Fibroin Scaffold with Chondrocytes - Taepavarapruk, Niwat; Tiyaboonchai, Waree; Chomchalao, Pratthana; Taepavarapruk, Pornnarin (Naresuan University Journal: Science and Technology (NUJST), 2017)
This study investigated the functional and histological properties of an implantation of silk fibroin/gelatin (SF/G) scaffold enriched with chondrocytes into a rat’s knee joint.  The animals were divided into 3 groups as 1) a sham group which received an incision on the joint capsule, 2) a blank SF/G group which had a burr hole on the cartilage and transplanted with a blank scaffold, and 3) SF/G+C group which had a burr hole on the cartilage and transplanted with chondrocyte-rich fibroin scaffold.  At the 1 st , 2 nd , 3 rd , and 4 th week after surgery, each animal was subjected to locomotor activity tests by running on a treadmill for 5 min and followed by climbing on a rotating rod for 5 min, respectively.  The results of treadmill test showed that some animals in each group could not walk or run as long duration as 5 min period in the 1 st week.  However, all of them could run normally on the treadmill in the 2 nd week.  For the rotarod test, most of the animals in SF/G+C group could not stay on a rotarod for the whole period of 5 min at the 1 st , 2 nd , 3 rd , and 4 th week after surgery.  In contrast, the results of sham and blank SF/G groups showed significantly longer duration of balancing on the rotarod.  Nevertheless, when compared the percent change of durations from the 1 st week to the 4 th week we found that the SF/G+C group had a greater improvement than the sham and blank SF/G groups.  After 1-month locomotor testing, the animals were euthanized and their right knees were kept in 10% formalin for at least 3 weeks, then decalcified in 10% nitric acid before slicing for the histological study.  By using H & E staining method, there was a thin layer of new regrowth tissue formed in the damaged bone of blank SF/G group.  In the SF/G+C group, however, there were a thicker layer of new regrowth tissue and a piece of scaffold with chondrocytes attached to the damage bone.  Altogether, these findings indicate that our silk fibroin/gelatin scaffolds have a high potential for further development to be the biocompatible biomaterial used for the treatment of injury or arthritic conditions of the articular surface. Keywords: bone regeneration, silk fibroin/gelatin scaffold, physical activity test
Keywords: bone regeneration; silk fibroin/gelatin scaffold; physical activity test